Randomised clinical trial research within Aboriginal and Torres Strait Islander primary health services: a qualitative study. Issue 12 (24th December 2021) - Abbott, Penelope; Askew, Deborah; Watego, Chelsea; Hu, Wendy CY; Campbell, Letitia; Tyson, Claudette; Walsh, Robyn; Hussey, Sylvia; Doyle, Kerrie; Gunasekera, Hasantha; Leach, Amanda Jane; Usherwood, Tim; et al.
Abstract : Objective: To better understand how to undertake valuable, ethical and sustainable randomised controlled clinical trial (RCT) research within Aboriginal and Torres Strait Islander primary health services. Design: In a qualitative approach, we utilised data collected between 2013 and 2020 during the planning and implementation of two RCTs. The data comprised agreed records of research meetings, and semistructured interviews with clinical trial stakeholders. The stakeholders were parents/carers of child participants, and site-based research officers, healthcare providers and community advisory groups. Our thematic analysis was informed by constructivist grounded theory. Setting: The RCTs investigated the management of otitis media in Aboriginal and Torres Strait Islander children, with the first RCT commencing recruitment in 2014 and the second in 2017. They took place in Aboriginal Medical Services (AMSs), large primary health services for Aboriginal and Torres Strait Islander people, based in urban and regional communities across two Australian states and one territory. Results: We analysed data from 56 meetings and 67 interviews, generating themes on making research valuable and undertaking ethical and sustainable RCTs. Aboriginal and Torres Strait Islander leadership, and support of AMSs in their service delivery function were critical. The broad benefits of the trials were considered important to sustainability, including workforce development, enhanced ear healthcare and multidirectional research capacity building. Participants emphasised the long-term responsibility of research teams to deliver benefits to AMSs and communities regardless of RCT outcomes, and to focus on relationships, reciprocity and creating positive experiences of research. Conclusion: We identify principles and strategies to assist in undertaking ethical and sustainable RCTs within Aboriginal and Torres Strait Islander primary health services. Maintaining relationships with AMSs and focusing on mutual workforce development and capacity building creates opportunities for long-term benefits so that health research and RCTs work for Aboriginal and Torres Strait Islander peoples, services, communities and researchers. Trial registration number: ACTRN12613001068752 (Pre-results); ACTRN12617001652369 (Pre-results).